The Level of Soluble FMS-Like Tyrosine Kinase 1 (sFlt-1) in the Umbilical Cord in Preeclampsia and its Correlation with Blood Pressure and Baby’s Birth Weight - Gusriani Gusriani; Nur Indah Noviyanti; Wahida Wahida (JURNAL INFO KESEHATAN, 2025)
Soluble FMS-like tyrosine kinase 1 (sFlt-1) is one of the markers that plays a role in the pathogenesis of preeclampsia. This study aimed to analyze the levels of umbilical cord sFlt-1 in relation to blood pressure and birth weight in babies on preeclamptic mothers. The study employed an analytical cross-sectional observational design. The sample size for this study consists of 33 participants. The levels of umbilical cord sFlt-1 were examined using the ELISA method. The data were analyzed using the Mann-Whitney U test to determine the differences in sFlt-1 levels, blood pressure, and birth weight. Spearman's rank correlation test was used to determine the correlation between sFlt-1 levels and blood pressure and birth weight. The sFlt-1 examination results indicated a significant difference between the preeclampsia and normal pregnancy groups. The mean sFlt-1 level in the preeclampsia group was 10.693 ng/mL (SD ±6.535 ng/mL), whereas in the normal pregnancy group, it was 3.572 ng/mL (SD ±1.225 ng/mL). This difference suggests that sFlt-1 levels are significantly higher in mothers with preeclampsia compared to those with normal pregnancies. This finding is consistent with the pathophysiology of preeclampsia, which involves endothelial dysfunction and an increase in anti-angiogenic factors such as sFlt-1.